Genetic Factors Associated With Nodulation and Nitrogen Derived From Atmosphere in a Middle American Common Bean Panel - Oladzad, Atena; González, Abiezer; Macchiavelli, Raul; de Jensen, Consuelo Estevez; Beaver, James; Porch, Tim; McClean, Phillip (Frontiers in Plant Science, 2020)
Among grain legume crops, common beans (Phaseolus vulgaris L.) are considered to have poor biological nitrogen fixation (BNF) capabilities although variation in nitrogen fixing capabilities exists within the species. The availability of genetic panel varying in BNF capacity and a large-scale SNP data set for common bean provided an opportunity to discover genetic factors associated with nitrogen fixation among genotypes in the Middle American gene pool. Using nodulation and percentage of nitrogen derived from atmosphere (% NDFA) data collected from field trials, at least 11 genotypes with higher levels of BNF capacity were identified. Genome wide association studies (GWAS) detected both major and minor effects that control these traits. A major nodulation interval at Pv06:28.0-28.27 Mbp was discovered. In this interval, the peak SNP was located within a small GTPase that positively regulates cellular polarity and growth of root hair tips. Located 20kb upstream of this peak SNP is an auxin-responsive factor AUX/IAA-related gene involved in auxin transportation during root nodulation. For % NDFA, nitrate transporters, NRT1:2 and NRT1.7 (Pv02:8.64), squamosa promoter binding transcriptome factor (Pv08:28.42), and MATE efflux family protein (Pv06:10.91) were identified as candidate genes. Three additional QTLs were identified on chromosomes Pv03:5.24 Mbp, Pv09:25.89 Mbp, Pv11: 32.89 Mbp. These key candidate genes from both traits were integrated with previous results on N2 fixation to describe a BNF pathway.